Cichlasoma urophthalmus (Günther 1862): discovery of alien predator fish in Kedung Ombo Reservoir, Central Java, Indonesia - Dadiono, Muh Sulaiman (Acta Aquatica: Aquatic Sciences Journal, 2023)
The entry of alien predatory fish in Indonesian waters has a negative impact on local ecosystems in Indonesia, foreign predatory fish can spread disease, become main predators and can cause imbalance in the food chain. From this study, we report the presence of alien predatory fish of the type Cichlasoma urophthalmus (Günther 1862) or Mayan Cichlid from tropical waters of North America caught in Kedung Ombo Reservoir, Grobokan Regency, Central Java. This finding is the first for the type of Cichlasoma urophthalmus recorded in the Kedung Ombo Reservoir. A description of the morphology of the caught species Cichlasoma urophthalmus is included in the discussion.Keywords: Cichlasoma urophthalmus, Mayan Cichlid, Alien Predatory Fish, Kedung Ombo Reservoir